Conditioning for figure skating : off-ice techniques for on-ice performance - Poe, Carl M. (Contemporary Books, 2002)
"Figure skating has evolved dramatically over the past few years, with a greater emphasis on triple and quadruple jumps, jump combinations, and dramatic lifts. And to stay competitive, skaters must spend hours developing their strength, power, flexibility, and endurance to perform these maneuvers. Conditioning for Figure Skating is a technical, user-friendly guide that teaches you how to improve your strength, increase your power, and condition your body off the ice to improve your on-ice performance." "Appropriate for skaters at all levels and all disciplines - singles, pairs, and ice dance - this guide explains the physical preparation needed to excel at the sport. Whether you are a skater, coach, trainer, or parent, you can use this book to establish a training structure and maximize skating potential."--BOOK JACKET.